Redbanded Thrips, Selenothrips rubrocinctus (Giard) (Insects: Thysanoptera: Thripidae): EENY-099/IN256, 6/1999 - Denmark, Harold A.; Wolfenbarger, D. O. (EDIS, 2002)
This document is EENY-099 (originally published as DPI Entomology Circular No. 108), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999. EENY-099/IN256: Redbanded Thrips, Selenothrips rubrocinctus (Giard) (Insects: Thysanoptera: Thripidae) (ufl.edu)